Among 'senators' and 'principes': historiographical forms and political action in the Principate - Dias, Mamede Queiroz (Romanitas - Revista de Estudos Grecolatinos, 2016)
This paper has two goals. The first one is to analyse how modern historiography understood the role of the Roman aristocracy between the first and second centuries of our era. The second one is to propose, using a passage in the Tiberian books of Tacitus’ Annals ways to analyse and explain the political acting of the urbs’ aristocracy into the public sphere in the imperial context.
Keywords: Roman Historiography; Principate; Politics; Public sphere; Tacitus